Analisis Hukum Dalam Pengawasan Perdagangan Pada E-Commerce Berdasarkan UU Nomor 5 Tahun 1999 - Handayani, Tri Astuti; Prabowo, Andrianto (Direktorat Penelitian dan Pengabdian (DPPM) Universitas Pelita Bangsa, 2025)
The rapid development of e-commerce poses challenges in trade supervision, including the potential for monopolistic practices and unfair business competition. This study aims to evaluate the effectiveness of existing regulations and provide policy recommendations to create a healthier and more competitive digital trade ecosystem. The method used is a juridical-normative approach with an analysis of regulations and cases of business competition in e-commerce. The results of the study show that although regulations are available, their implementation and supervision still face obstacles, such as low awareness of business actors regarding legal regulations and lack of coordination between supervisory institutions. Therefore, it is necessary to strengthen regulations, educate business actors and consumers, and increase supervision based on digital technology to ensure compliance with competition law. This study is expected to be a reference in developing policies and law enforcement in digital trade in Indonesia